Muslim Consumers' Preferences on Interest in Buying Halal Food and Beverage Products with moderating variables of gender and education in DKI Jakarta - Firdayetti; Basri, Yuswar Zainul; Arafah, Willy (APTISI Transactions on Management (ATM), 2023)
The purpose of this study was to analyze the preferences of Muslim consumers towards buying interest in Halal Food and Beverage Products in DKI Jakarta. The independent variables are Price, Islamic Brand, Product Knowledge and Religious Knowledge with the dependent variable being Product Halal Intention with the variable gender and education moeration.  Methodology used is quantitative with SEM AMOS analysis tool, the population is DKI Jakarta society, with 225 respondents aged 17 years and over who are Muslims as consumers of halal food and beverages as the sample. with the intent of the research. The results of the study directly have two variables that affect the halal intention of the product (product knowledge and religious knowledge on the halal intention of the product) and the second variable has no effect on the halal intention of the product (price and Islamic brand on the halal intention of the product). If using the moderating variables of gender and education, the four independent variables (price, Islamic brand, product knowledge and religious knowledge) have an effect on product halal intentions. The theoretical conclusion is that only 2 out of 4 variables congruent with the theory and the two are not congruent with the theory Administrative influences are applied based on consumer preferences as follows: Religious knowledge of prices, Islamic brands, product knowledge and  halal products Intent when there are modulating variables.